2011
DOI: 10.1371/journal.pone.0017498
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Proteomic Analysis of the Impact of Mitotic Quiescence on the Engraftment of Human CD34+ Cells

Abstract: It is well established that in adults, long-term repopulating hematopoietic stem cells (HSC) are mitotically quiescent cells that reside in specialized bone marrow (BM) niches that maintain the dormancy of HSC. Our laboratory demonstrated that the engraftment potential of human HSC (CD34+ cells) from BM and mobilized peripheral blood (MPB) is restricted to cells in the G0 phase of cell cycle but that in the case of umbilical cord blood (UCB) -derived CD34+ cells, cell cycle status is not a determining factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Functional characteristics of HSPCs, such as homing, engraftment, cell cycle status, and self-renewal activity vary according to their tissue of origin (14,48). For example, circulating blood stem cells can not compete effectively against bone marrow-derived stem cells for long-term multilineage repopulation (49).…”
Section: Discussionmentioning
confidence: 99%
“…Functional characteristics of HSPCs, such as homing, engraftment, cell cycle status, and self-renewal activity vary according to their tissue of origin (14,48). For example, circulating blood stem cells can not compete effectively against bone marrow-derived stem cells for long-term multilineage repopulation (49).…”
Section: Discussionmentioning
confidence: 99%
“…More recent analysis of the genomic and proteomic variation in the mitotic state of CD34 + cells derived from bone marrow, peripheral blood, and cord blood has also indicated the unique nature of cord blood cells. Analysis of 484 target genes and 646 proteins [24] showed that engraftment potential of bone marrow or peripheral blood cells was only evident in the G0 phase of the cell cycle, whereas in cord blood, cell cycle status was not a limiting factor in engraftment potential. Research by Jin et al (2013) confirms that mesenchymal stromal cells derived from cord blood have significantly higher clonality (and lower expression of cell senescence markers) than those derived from bone marrow [25].…”
Section: Discussionmentioning
confidence: 99%
“…An example is the increasing use of new "mobilizing" agents such as plerixafor in addition to G-CSF, which leads to a higher content of more primitive progenitor cells in PB grafts [23]. Recent results suggest that genomic and proteomic analysis may become important, since mitotic quiescence and differential gene expression patterns appear to be significant for engraftment [24]. Further recent findings are that the genotype of Ig-like receptor on donor natural killer cells has impact on both immunity status and infections [25] and relapse-free survival after unrelated HPC transplantation for acute myeloid leukemia [26].…”
Section: Discussionmentioning
confidence: 99%